KETERAMPILAN SOSIAL ANAK DALAM KELAS MULTIKULTURAL DI PAUD ROSELLA PONTIANAK UTARA - Desi Retnosari; Muhamad Ali; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe aim of this research was to describe the social skills of children in multicultural classes at PAUD Rosella Northern Pontianak. The method use in this research is descriptive method with a qualitative research approach. Data subjects in this research are 15 childern in PAUD Rosella Northern Pontianak.. The techniques used in this research were observation and documentation using data collection tools like is observation guidelines, and documentation picture. The results of data analysis show that social skills of children in multicultural classes at PAUD Rosella Northern Pontianak are good.Emphaty attitude of children in multicuktural classes is good, especially in attentive attitude, tolerance, caring for the others without discriminating religion,can be seen from the child wants to listen to his friends who talk or telling stories. Positive habituation in multicultural classes is good, especially in manners, social responbility, and independence.Can be seen from children using polite language when talking with others,the child apologize when they make mistakes, the child say thank you when helped,the child tidy up their toys after they finish playing.Keyword          : Children, Social Skills, Multicultural